Carboranylphosphinic Acids: A New Class of Purely Inorganic Ligands. Issue 11 (7th January 2016) - Oleshkevich, Elena; Teixidor, Francesc; Choquesillo‐Lazarte, Duane; Sillanpää, Reijo; Viñas, Clara
Abstract: Purely inorganic carboranyl phosphinates were prepared, and the influence of the cluster on the reactivity of the phosphinate group was studied. Electron‐withdrawal by the carboranyl carbon atoms, combined with space‐filling efficiency and enhanced aromaticity of the cluster cage, renders the phosphorus more difficult to oxidize. This enables carboranyl phosphinates to survive harsh oxidizing conditions, a property which is uncommon in organic phosphinates. Abstract : Purely inorganic carboranyl phosphinates were prepared and the influence of the cluster on the reactivity of the phosphinate group was studied (see figure). Electron‐withdrawal by the carboranyl carbon atoms, combined with space‐filling efficiency and enhanced aromaticity of the cluster cage, renders the phosphorus more difficult to oxidize. This enables carboranyl phosphinates to survive harsh oxidizing conditions.